A survey of the pharmaceutical services offered by the pharmacies and drugstores of the Municipality of Toledo, Paraná State, Brazil (Research, Society and Development, 2020)
This study aimed to survey the pharmaceutical services provided by pharmacies and drugstores in the city of Toledo/PR and to analyze the quality of the services offered. A cross-sectional descriptive study was carried out in 64 pharmacies and drugstores of Toledo/PR, between June and July of 2017. All cases were published twice. At the first visit, through a questionnaire, the pharmacist answered of the services provided and about the conditions under the services are performed. During the second visit, it was verified which services the establishment was authorized to perform, as described in the sanitary license, the accomplishment of the service in the dispensation area and movement of people, the pharmacist presence and the provision of services not allowed. It was concluded that the vast majority of establishments provided pharmaceutical services to the population under acceptable conditions. However, in some cases, the pharmacist was not present to oversee the procedures, the service was performed in an inappropriate location, irregularly and / or did not provide the declaration of pharmaceutical services to the patient.